Hubungan Obesitas dengan Kejadian Hipertensi pada Dosen Fakultas Kedokteran Universitas Islam Bandung Tahun 2023 - Efendi Rosedevi; Yuli Susanti; Susan Fitriyana (Bandung Conference Series: Medical Science, 2024)
Abstract. The world of health is currently experiencing an epidemiological transition where Non-Communicable Diseases (NCDs) are one of the concerns in the world. Hypertension is one of the NCDs with the most sufferers, as many as 1.13 billion people with hypertension worldwide. One of the risk factors that cause hypertension is obesity. Obesity can cause an increase in Sympathetic Nervous System (SNS) activity which causes sodium retention in the blood vessels, increasing blood volume and pressure in the blood vessels. This study aims to determine the relationship between obesity and the incidence of hypertension in lecturers at the Faculty of Medicine, Islamic University of Bandung in 2023. This study is a quantitative study with an observational analytic research design conducted at the Faculty of Medicine, Islamic University of Bandung using simple random sampling techniques in the population, the research sample comes from primary data in the form of measurement results of body weight, height, and blood pressure. Data were analyzed by univariate and bivariate analysis and fisher’s exact test. The number of respondents was 44 people with the characteristics of the majority of respondents being female, age more than equal to 35 years. The majority of respondents were obese (52.2%) and had normal blood pressure (43.2%). The results of this research obtained a p-value of 0.105 which indicates that there is no relationship between obesity and the incidence of hypertension in lecturers at the Faculty of Medicine, Islamic University of Bandung in 2023. Abstrak. Dunia kesehatan saat ini mengalami transisi epidemiologi dimana Penyakit Tidak Menular (PTM) menjadi salah satu perhatian di dunia. Hipertensi merupakan salah satu PTM dengan penderita terbanyak, yaitu sebanyak 1,13 miliar penderita hipertensi di seluruh dunia. Faktor risiko yang menyebabkan terjadinya hipertensi salah satunya obesitas. Kondisi obesitas dapat menyebabkan peningkatan aktivitas Sympathetic Nervous System (SNS) yang menyebabkan retensi natrium di dalam pembuluh darah, meningkatkan volume darah dan tekanan di dalam pembuluh darah. Penelitian ini bertujuan untuk mengetahui hubungan obesitas dengan kejadian hipertensi pada dosen Fakultas Kedokteran Universitas Islam Bandung tahun 2023. Penelitian ini merupakan penelitian kuantitatif dengan desain penelitian analitik observasional yang dilakukan di Fakultas Kedokteran Universitas Islam Bandung menggunakan teknik simple random sampling pada populasi, sampel penelitian berasal dari data primer berupa hasil pengukuran berat badan, tinggi badan, dan tekanan darah. Data dianalisis dengan analisis univariat dan bivariat serta dilakukan uji fishers exact. Jumlah responden sebanyak 44 orang dengan karakteristik responden mayoritas berjenis kelamin perempuan, usia lebih dari sama dengan 35 tahun. Mayoritas responden berada pada kondisi obesitas (52.2%) dan berada pada kondisi tekanan darah normal (43.2%). Hasil penelitian ini didapatkan p-value sebesar 0.105 yang menunjukkan tidak terdapat hubungan antara obesitas dengan kejadian hipertensi pada dosen Fakultas Kedokteran Universitas Islam Bandung tahun 2023.